ANALISIS KONSEP FISIKA PADA PENGGUNAAN ALAT PERTANIAN CANGKUL OLEH PETANI SEBAGAI BAHAN PEMBELAJARAN FISIKA - Muhammad Faizal Arifi; Albertus Djoko Lesmono; Rif'ati Dina Handayani (Universitas Jember, 2021)
Indonesia is an agricultural country so there are still many agricultural environments. One of the implementations of the agricultural sector in education, it’s can be applied to vocational high schools agriculture major. Students learning activities in this major can be integrated with their practical activities in the agricultural sphere, because learning physics will be more attractive to students if the learning activities in the classroom also linked with students daily experience and environment. Within the scope of agriculture, agricultural tools are closely related to the concept of physics, one of which is the hoe. So the purpose of this research is to describe the physics concepts analysis on the use of hoe by farmers, then designed a draft of physics learning materials. This research is descriptive qualitative research using content analysis method to obtain the results that in the use of hoe there are several physics concepts about mechanics including the concept of force, rotational dynamics, work and energy. Then processed into a draft of physics learning materials for students of vocational high school class X in agribusiness and agrotechnology major, by adjusting the relevant basic competencies, namely KD 3.4 on work and energy, and KD 3.6 on rotational dynamics.